Predictors and perinatal outcomes of pre-labor rupture of membrane among pregnant women admitted to Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia: a retrospective study - Wolde, Meseret; Mulatu, Teshale; Alemayehu, Gemechu; Alemayehu, Afework; Assefa, Nega (Frontiers in Medicine, 2024)
Background Pre-labor rupture of membrane (PROM) refers to a membrane rupture that occurs after the 28th week of pregnancy but before the start of labor. If not appropriately managed, it poses a significant risk to the health of the mother and fetus. However, information on the magnitude of PROM, contributing factors, and its perinatal outcomes was limited in Eastern Ethiopia. This study assessed the prevalence, predictors, and perinatal outcomes of PROM among pregnant women admitted to Hiwot Fana Comprehensive Specialized University Hospital (HFCSUH) in Eastern Ethiopia so as to guide specific preventive measures. Methods A hospital-based retrospective cross-sectional study was carried out from May 15 to June 14, 2022, and data were gathered by reviewing the chart records of 424 pregnant women who were admitted to maternity and labor wards in the previous two years, from January 1, 2019 to December 31, 2020. Records were chosen using a simple random sampling method. Mother’s socio-demographic traits, previous obstetric and gynecologic history, current pregnancy history, habit-related history (khat chewing), ultrasound findings, laboratory investigations, mode of delivery, maternal and perinatal outcomes were extracted from the maternal charts. Bi-variable and multivariable logistic regression analyses were performed to identify predictors of pre-labor membrane rupture. The association between the explanatory and outcome variables was expressed using an adjusted odds ratio with a 95% confidence interval. Results The prevalence of pre-labor membrane rupture was 16.27% with 95% CI: (13.05–20.11). Among 69 women who experienced pre-labor rupture of membrane, 50 (72.5%) of them had adverse perinatal outcomes. Of all 69 neonates 17 (24.64%) were delivered with low birth weight and 20 (29%) of them were born preterm. The overall perinatal mortality rate was 10.1% or 101 per 1,000 live births. History of abortion [AOR = 2.61; 95% CI (1.09, 6.24)], urinary tract infection [AOR = 2.59; 95% CI (1.23, 5.42)], antepartum hemorrhage [AOR = 3.35; 95% CI (1.38, 8.13)], and khat chewing (a leafy plant which contains psychoactive chemical) in the current pregnancy [AOR = 2.63; 95% CI (1.49, 4.63)] were all significantly associated with pre-labor rupture of membrane. Conclusion In this study, the magnitude of pre-labor membrane rupture was relatively high compared to the global rate. Prenatal risk identification and early detection of complications among mothers with a history of abortion, antepartum hemorrhage, urinary tract infection, and counseling on the effects of khat chewing during pregnancy are crucial to reduce the likelihood of pre-labor membrane rupture and its adverse perinatal outcome.